DAMPAK PENGEMBANGAN PERKEBUNAN KAKAO RAKYAT MELALUI P2WK TERHADAP DISTRIBUSI PENDAPATAN DI KABUPATEN DONGGALA SULAWESI TENGAH - Novia Dewi (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
The policy objective for cacao agribusiness development in the province of Central Sulawesi was directed toward the improvement of production, farm income and employment. In fact, there numerous cases such as scarcity and high prices of inputs, and farmer’s limited capital have become obstacles in these efforts,. The objective of this study was to evaluate the effect of P2WK project upon income of the cacao farm and its respected income distribution. The results of this study indicated that the P2WK project had affected upon income improvement through better land use, fertilizer, pesticide and the use of non-household labor, but then it was followed by disproportionate distribution of their income.